Branched Pectic Galactan in Phloem-Sieve-Element Cell Walls: Implications for Cell Mechanics . Issue 2 (17th November 2017) - Torode, Thomas A.; O'Neill, Rachel; Marcus, Susan E.; Cornuault, Valérie; Pose, Sara; Lauder, Rebecca P.; Kračun, Stjepan K.; Rydahl, Maja Gro; Andersen, Mathias C. F.; Willats, William G. T.; Braybrook, Siobhan A.; Townsend, Belinda J.; et al.
Abstract : Branched pectic galactan is identified as a component of the cell walls of phloem sieve elements. Abstract: A major question in plant biology concerns the specification and functional differentiation of cell types. This is in the context of constraints imposed by networks of cell walls that both adhere cells and contribute to the form and function of developing organs. Here, we report the identification of a glycan epitope that is specific to phloem sieve element cell walls in several systems. A monoclonal antibody, designated LM26, binds to the cell wall of phloem sieve elements in stems of Arabidopsis ( Arabidopsis thaliana ), Miscanthus x giganteus, and notably sugar beet ( Beta vulgaris ) roots where phloem identification is an important factor for the study of phloem unloading of Suc. Using microarrays of synthetic oligosaccharides, the LM26 epitope has been identified as a β-1, 6-galactosyl substitution of β-1, 4-galactan requiring more than three backbone residues for optimized recognition. This branched galactan structure has previously been identified in garlic ( Allium sativum ) bulbs in which the LM26 epitope is widespread throughout most cell walls including those of phloem cells. Garlic bulb cell wall material has been used to confirm the association of the LM26 epitope with cell wall pectic rhamnogalacturonan-I polysaccharides. In the phloem tissues of grass stems, the LM26 epitope has a complementary pattern to that of the LM5 linear β-1, 4-galactan epitope, which is detected only in companion cell walls. Mechanical probing of transverse sections of M . x giganteus stems and leaves by atomic force microscopy indicates that phloem sieve element cell walls have a lower indentation modulus (indicative of higher elasticity) than companion cell walls.